Measurement of the t(t)over-bar production cross section in the dilepton channel in pp collisions at root s=7 TeV - Chatrchyan, S. (2012)
The t (t) over bar production cross section (sigma(t (t) over bar)) is measured in proton-proton collisions at root s = 7 TeV in data collected by the CMS experiment, corresponding to an integrated luminosity of 2.3 fb(-1). The measurement is performed in events with two leptons (electrons or muons) in the final state, at least two jets identified as jets originating from b quarks, and the presence of an imbalance in transverse momentum. The measured value of sigma(t (t) over bar) for a top-quark mass of 172.5 GeV is 161.9 +/- 2.5 (stat.)(-5.0)(+5.1) (syst.) +/- 3.6 (lumi.) pb, consistent with the prediction of the standard model.